Age-related relationship between the development of hyperplastic processes and VEGF expression in endometrial cells - Z. V. Chumak; M. V. Shapoval; V. V. Artyomenko (Kazimierz Wielki University, 2020)
The existence of a clear tendency to increase the prevalence of hormone-dependent diseases and endometrial cancer against the background of increasing the frequency of their occurrence and rejuvenation of the age of manifestation leads to the search for new possible markers of diagnosis and prognosis of the development of pathological process. Angiogenesis is one of the forms that lead to the formation of new blood vessels, with an increased metabolic need for perfusion of existing vessels. The vascular endothelial growth factor family (VEGF) is a protein that is the major inducer of angiogenesis. The objective: To study the expression of VEGF in endometrial cells in proliferative, hyperplastic, atrophic states at women's different ages. Materials and methods. A retrospective analysis of medical records of the pathohistological bureau for the period 2014-2016 was conducted. 2196 pathomorphological findings of endometrial tissue specimens have been examined. Estimation of VEGF expression was performed in 417 endometrial specimens, in the cohorts of the study: in the reproductive, perimenopausal, postmenopausal periods, respectively, in groups with physiological endometrial proliferation phase, hyperplastic, atypical, atrophic endometrium. The results were statistically processed. Results and discussion. Analyzing the data presented, higher VEGF expression was detected in atypical hyperplasia in all age categories, but it was likely that higher rates were established in the postmenopausal period, with atypical endometrial hyperplasia, suggesting physicians' alertness to the process in this category.  Probably low were indexes found at atrophic endometrium in this age category, which confirms the endometrial preservation of its growth factors, and in the presence of processes that stimulate the proliferation of the organ, they can trigger at the molecular-genetic level, neoplastic mechanisms. The data of the retrospective analysis confirm the growth of atypical form of hyperplastic processes and their maximum detection in the age categories 41 - 45  and 46 - 50 years old, and the beginning of detection of endometrial malignancy from the age of 46 - 50 years old, with a gradual increase with age. Conclusions. Expression of VEGF level in endometrial tissue cells as an inducer of angiogenesis can be a promising marker for the diagnosis of the risk of proliferative conditions and their prognosis, especially in relation to other markers characterizing immunohistochemical and molecular genetic cellular parameters.